Comparative study of simple interline and three-way cross maize hybrids - G. Ya. Krivosheev; A. S. Ignatiev; D. R. Lupinoga; Yu. B. Arzhenovskaya (Зерновое хозяйство России, 2022)
Domestic interline maize hybrids are predominantly three-way cross hybrids in structure, and foreign breeding and seed companies prefer simple interline hybrids. In order to improve the competitiveness of domestic breeding, it is necessary to reorient to simple hybrids, which, in turn, requires information on whether simple maize hybrids have an advantage in specific soil and climatic areas. The purpose of the current study was to conduct a comparative study of new simple interline and three-way cross maize hybrids according to grain productivity and uniformity of economically valuable traits under unstable moisture supply. The study was carried out on the experimental field of crop rotation of the laboratory for maize breeding and seed production of the FSBSI “ARC Donskoy” in 2019–2021. The objects of the study were 10 simple and 10 three-way cross new domestic maize hybrids developed by the method of complete topcrosses. The establishment of field trials, records, biometric measurements and phenological observations were conducted in accordance with the methodological recommendations for conducting field trials with maize. There has been found that productivity of simple hybrids (3.49–4.65 t/ha) turned out to be significantly larger than that of three-way cross hybrids (2.84–3.70 t/ha), the mean excess was 0.78 t/ha or 23.6 %. Simple hybrids were characterized with the best uniformity in a length of a vegetation period (V = 0.58–2.13 %), height of maize ear attachment (V = 5.0–11.3 %), plant height (V = 2.8–4.8 %), and, consequently, better harvesting adaptability. There has been found a negative mean correlation (r = –0.49...–0.69) between grain productivity and variation of traits in terms of maturation, plant height and height of maize ear attachment. There has been found no correlation between the structure of interline maize hybrids and such traits as grain harvest moisture, resistance to lodging and smut “virus”. Due to a set of traits there has been identified a new simple interline maize hybrid ‘Zernogradsky 367’.